Nitrogen Intake and Excretion in Male Kacang Goats Receiving Feed With Different Energy Levels - Hoar, Matilda; Tahuk, Paulus Klau; Nahak, Oktovianus R. (Journal of Tropical Animal Science and Technology, 2025)
This study aims to determine the nitrogen intake and excretion status of male Kacang goats that receive feed with different energy levels. The study was conducted for three months in the livestock experimental pen of the Faculty of Agriculture, Science and Health, University of Timor Kefamenanu, North Central Timor Regency. Nine male Kacang goats with an initial body weight of 11 to 13 kg and aged between 6 and 12 months were divided into three groups, each group representing a different treatment. The treatments were: T1 = livestock obtained an energy level of 65%, + CP 15%, T2 = livestock obtained an energy level of 67%, + CP 15%, and T3 = livestock obtained an energy level of 70%, + CP 15%.The variables measured consisted of nitrogen consumption, fecal nitrogen and urine nitrogen. The results of the study showed that the highest nitrogen consumption in the T3 treatment was 3.2033 ± 0.1549 g/head/day, followed by the T2 treatment of 3.0894 ± 0.0384 g/head/day, and the T1 treatment of 2.6159 ± 0.0658 g/head/day; fecal nitrogen in the T1 treatment was 1.5070 ± 0.3880 g/head/day, followed by the T3 treatment of 1.1673 ± 0.2751 g/head/day, and the T2 treatment of 1.1566 ± 0.5887 g/head/day; urinary nitrogen in the T2 treatment was 0.7906 ± 0.1804 g/head/day, followed by the T1 treatment of 0.7606 ± 0.0456 g/head/day and the T3 treatment of 0.6933 ± 0.0637 g/head/day.   The results of the analysis of variance showed that the treatment had a significant effect on nitrogen consumption and had no significant effect on fecal nitrogen and urinary nitrogen. It was concluded that feeding with different energy levels could increase nitrogen intake but relatively the same fecal and urinary nitrogen excretion. Keywords: Nitrogen Intake, Nitrogen Excretion, Kacang Goat, Energy Level